A mutation in the epithelial sodium channel causing Liddle disease increases channel activity in the Xenopus laevis oocyte expression system. - Schild, L (1995)
We have studied the functional consequences of a mutation in the epithelial Na+ channel that causes a heritable form of salt-sensitive hypertension, Liddle disease. This mutation, identified in the original kindred described by Liddle, introduces a premature stop codon in the channel beta subunit, resulting in a deletion of almost all of the C terminus of the encoded protein. Coexpression of the mutant beta subunit with wild-type alpha and gamma subunits in Xenopus laevis oocytes resulted in an approximately 3-fold increase in the macroscopic amiloride-sensitive Na+ current (INa) compared with the wild-type channel. This change in INa reflected an increase in the overall channel activity characterized by a higher number of active channels in membrane patches. The truncation mutation in the beta subunit of epithelial Na+ channel did not alter the biophysical and pharmacological properties of the channel--including unitary conductance, ion selectivity, or sensitivity to amiloride block. These results provide direct physiological evidence that Liddle disease is related to constitutive channel hyperactivity in the cell membrane. Deletions of the C-terminal end of the beta and gamma subunits of rat epithelial Na+ channel were functionally equivalent in increasing INa, suggesting that the cytoplasmic domain of the gamma subunit might be another molecular target for mutations responsible for salt-sensitive forms of hypertension.